PENGARUH PROGRAM BINCANG PAGI RADIO REPUBLIK INDONESIA BENGKALIS 90,6 FM TERHADAP MINAT PENDENGAR MASYARAKAT KECAMATAN BENGKALIS KABUPATEN BENGKALIS - Wijiati "; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Radio media is certainly no stranger to the people of Indonesia, both from the lower classes and above, both young and old. For some people listening to radio has become a necessity. Those who are busy or who do not have time to watch television or read newspapers will depend on the radio as a source of information. This study uses the SOR theory which assumes that communication is a reaction action process involving humans. The purpose of this study was to find out how much influence the morning talk program radio republic of indonesia FM 90.6 Bengkalis had on the interest of listeners in the Bengkalis district of Bengkalis district.            This type of research is quantitative research with explanatory methods. The researcher collected the data using a questionnaire or questionnaire covered in an online manner and through the google form. The location of this study is in the district of Bengkalis, Bengkalis Regency. Sampling was done by purposive sampling using unknwon population formula and a sample of 100 respondents was obtained. The researcher used person product moment correlation analysis the questionnaire data processing was carried out using the Windows version 21 Program Statistics of Service Solution (SPSS).            The results of this study obtained a regression coefficient Y = 8.256 + 0.280 X with a significance level of 0.001 smaller than α = 0.05. it means that there is the Influence of the Morning Radio Talk Program of the Republic of Indonesia FM 90.6 Bengkalis Against the Interest of the Listener Community of Bengkalis Sub-District, Bengkalis Regency by 13,6% which is categorized as having a low level of influence. Thus Ho  is rejected and Ha  is accepted.